Analysis of Factors Affecting Credit Quality (Case Study at PT. Bank Rakyat Indonesia (Persero) Tbk) - Yuniarti, Rita; Sukmawaty, Namirah; Rini, Adistyo; Sinaga, Obsatar (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study discusses the factors that affect credit quality in the banking world. This research uses descriptive analysis method. The data in this study used primary and secondary data. The results showed that the credit disbursement did not focus on the knowledge of bank officials towards the type of debtor's business. While, credit disbursement policy, data analysis and future predictions, the implementation of credit coaching and supervision of debtors, the debtor’s economic activities and debtor's faith are the main factors in the implementation of credit lending activities. Credit quality at PT. Bank Rakyat Indonesia (Persero) Tbk in the pandemic period is still quite good as seen from the highest Non-Performing Loan (NPL) value of 3.27 in June 2021. Meanwhile, the NPL value limit set by OJK for the pandemic period was increased to 5%.